Laser and Fiber Electronics Group - Sotor, Jarosław; Abramski, Krzysztof; Antończak, Arkadiusz; Sobon, Grzegorz; Kaczmarek, Paweł; Wąż, Adam; Dudzik, Grzegorz; Krzempek, Karol; Stępak, Bogusz; Sterczewski, Łukasz; Stachowiak, Dorota; Boguslawski, Jakub; et al. (Photonics Letters of Poland, 2019)
The Laser & Fiber Electronics Group (LFEG) constitutes a team of young, skilled and ambitious researchers, doctoral candidates and students. The Group possesses great experience in applied optoelectronics and laser technology. Currently, it conducts research in several areas,mostly focusing on: ultrashort laser pulse generation using novel materials, development of pulsed fiber laser sources ranging from visible to mid-infrared, development of compact mid-infrared optical frequency combs, laser spectroscopy techniques, laser vibrometry, solid-state lasers, advanced analog and digital electronics, and investigations of light-matter interaction.